LINGUISTIC AND CULTURAL DIFFERENCES IN THE PROCESS OF TRANSLATION - Bobokulova Dilnoza Bakhtiyor kizi (Western European Studies, 2025)
This thesis investigates the difficulties and solutions involved in the art and science of translation, examining the linguistic, cultural, and contextual obstacles that translators encounter. The research highlights various translation issues and suggests effective strategies to improve the accuracy, fluency, and cultural appropriateness of translations, with the goal of promoting effective communication across different linguistic and cultural contexts. The challenges of translating foreign texts and terminology in various sectors are rapidly evolving, reflecting the increasing interest from users and developers in specific terms. A significant and urgent challenge in dealing with foreign texts in this field is selecting an appropriate equivalent for newly emerging concepts. The most crucial and informative words that convey the primary meaning in this context are terms.
Keywords: primary; translation; interpreting; contextual